2009
DOI: 10.1111/j.1600-0722.2009.00662.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antimicrobial effect of photodynamic antimicrobial therapy in an in situ model of dentine caries

Abstract: Photodynamic antimicrobial therapy (PACT) promotes bacterial death as a result of the photosensitization of microbial components. This study evaluated the effect of PACT on dentine caries produced in situ. Over the course of 14 d, 20 volunteers wore intra-oral devices containing human dentine slabs that were treated 10 times daily with a 40% sucrose solution. Afterwards, the antimicrobial effect of toluidine blue O, associated with 47 or 94 J cm(-2) of a light-emitting diode, was evaluated. Before and after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
109
1
17

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 139 publications
(129 citation statements)
references
References 64 publications
2
109
1
17
Order By: Relevance
“…Similar results have been shown in previous studies using different photosensitizers on oral bacteria. [38][39][40][41] One of the main observations made during the first tests to photoinactivate bacteria with conventional photosensitizers was the relative sensitivity of gram-positive strains to photodynamic inactivation. 24 This sensitivity was confirmed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been shown in previous studies using different photosensitizers on oral bacteria. [38][39][40][41] One of the main observations made during the first tests to photoinactivate bacteria with conventional photosensitizers was the relative sensitivity of gram-positive strains to photodynamic inactivation. 24 This sensitivity was confirmed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…After incubation, the number of Streptococcus mutans was determined by colony counting, and the values were expressed as colony forming units (CFU) per milligram of dentin [18].…”
Section: Carious Dentin Microbial Analysismentioning
confidence: 99%
“…Results of several studies demonstrated an antibacterial effect of PDT on oral bacteria in biofilms [13,14] and in dentine carious lesions [9,[15][16][17][18]. However, none of those studies used curcumin as a PS to kill cariogenic bacteria.…”
Section: Introductionmentioning
confidence: 99%